Anaerobic biofilter reactor to treat palm oil mill effluent (POME) - Baharin, Badlishah Sham; Yahya, A. B.; Megat Mohd Noor, Megat Johari (1987)
An initial design of an anaerobic biofilter reactor was carried out for application in the treatment of palm oil mill effluent (POME). The parameters of the design were based on the results of laboratory tests using a 2-litre model reactor. The operation was carried out at room temperature. The anaerobic biofilter reactor designed was cylindrial in shape with a capacity of 12 litres and fabricated from clear perspex. The filter media used were Polyvinylchloride (PVC) rings which had a diameter of 1.2cm to 2.0cm. The specific area of the filter media was 80m2/m3 and the porosity value was 0.93. Tests were carried out on the reactor with an organic inflow rate of 2.1kg COD/m3-day and a feed flowrate of 1.2 litres to 2.8 litres/day. The pH was maintained at 6.5 to 7.4. The results of the initial tests showed that the reactor had an efficiency of about 60% in reducing the COD level of the POME. The suitable retention time for operation of the reactor was found to be 6 to 9 days when the reactor was maintained at 28c.